Public sector of Canada: rating research of labour - Totska, Olesia Leontiivna; Тоцька, Олеся Леонтіївна (The Annals of the Stefan cel Mare University of Suceava, Fascicle of the Faculty of Economics and Public Administration, 2013)
In this article an author conducted the analysis of labour in the public sector of Canada after such nine sub-groups of establishments: 1) federal general government; 2) provincial and territorial general government; 3) health and social service institutions (provincial and territorial); 4) universities, colleges, vocational and trade institutes (provincial and territorial); 5) local general government; 6) local school boards; 7) federal government business enterprises; 8) provincial and territorial government business enterprises; 9) local government business enterprises. On the basis of statistical information about these sub-groups for 2007-2011 from a web-site «Statistics Canada» the maximal and minimum values of such three indexes are found: amount of employees, general annual sums of wages and annual sums of wages per employee. Rating for nine sub-groups of establishments of public sector of Canada on these indexes is certain. The got results testify, that during an analysable period most of the employees of public sector was concentrated in health and social service institutions, the least – in local government business enterprises. In 2007–2011 a most general sum was earned also by the employees of health and social service institutions, the least – by the employees of local government business enterprises. At the same time in an analysable period among the state employees of Canada a most wage in a calculation on one person was got by the employees of federal general government, the least – by the employees of local general government. У цій статті автор провів аналіз праці в державному секторі Канади за такими дев’ятьма підгрупами установ: 1) федеральний генеральний уряд; 2) провінційний і територіальний генеральний уряд; 3) заклади здоров’я та соціального сервісу (провінційні та територіальні); 4) університети, коледжі, професійні та торгові інститути (провінційні та територіальні); 5) місцевий генеральний уряд; 6) місцеві шкільні правління; 7) федеральні урядові комерційні підприємства; 8) провінційні та територіальні урядові комерційні підприємства; 9) місцеві урядові комерційні підприємства. На основі статистичної інформації про ці підгрупи за 2007–2011 роки із сайту «Статистика Канади» знайдено максимальні та мінімальні значення таких трьох показників: кількість працівників, загальні річні суми заробітків і річні суми заробітків на одного працівника. Визначено рейтинги для дев’яти підгруп установ державного сектора Канади за цими показниками. Отримані результати свідчать про те, що протягом аналізованого періоду найбільша кількість працівників державного сектору була зосереджена в закладах здоров’я та соціального сервісу, найменша – у місцевих урядових комерційних підприємствах. У 2007–2011 роках найбільшу загальну суму було зароблено також працівниками закладів здоров’я та соціального сервісу, найменшу – працівниками місцевих урядових комерційних підприємств. Водночас в аналізованому періоді серед державних працівників Канади найбільшу заробітну плату в розрахунку на одну особу отримували працівники федерального генерального уряду, найменшу – працівники місцевого генерального уряду.
Державний сектор Канади: рейтингове дослідження праці
Keywords: Canada; Канада; public sector; державний сектор; workers; працівники; wages; оклади; ratings; рейтинги